Targeted nanomedicine for prostate cancer therapy: docetaxel and curcumin co-encapsulated lipid–polymer hybrid nanoparticles for the enhanced anti-tumor activity in vitro and in vivo. (12th June 2016) - Yan, Jieke; Wang, Yuzhen; Zhang, Xufeng; Liu, Shuangde; Tian, Chuan; Wang, Hongwei
Abstract: Objective : Docetaxel (DTX) remains the only effective drug for prolonging survival and improving quality of life of metastatic castration-resistant prostate cancer (mCRPC) patients. Combination anticancer therapy encapsulating DTX and another extract of traditional Chinese medicine is one nano-sized drug delivery system promising to generate synergistic anticancer effects, to maximize the treatment effect, and to overcome multi-drug resistance. The purpose of this study is to construct lipid–polymer hybrid nanoparticles (LPNs) as nanomedicine for co-encapsulation of DTX and curcumin (CUR). Methods : DTX and CUR co-encapsulated LPNs (DTX-CUR-LPNs) were constructed. DTX-CUR-LPNs were evaluated in terms of particles size, zeta potential, drug encapsulation, and drug delivery. The cytotoxicity of the LPNs was evaluated on PC-3 human prostate carcinoma cells (PC3 cells) by MTT assays. In vivo anti-tumor effects were observed on the PC3 tumor xenografts in mice. Results : The particle size of DTX-CUR-LPNs was 169.6 nm with a positive zeta potential of 35.7 mV. DTX-CUR-LPNs showed highest cytotoxicity and synergistic effect of two drugs in tumor cells in vitro. In mice-bearing PC-3 tumor xenografts, the DTX-CUR-LPNs inhibited tumor growth to a greater extent than other contrast groups, without inducing any obvious side effects. Conclusion : According to these results, the novel nanomedicine offers great promise for the dual drugs delivery to the prostate cancer cells, showing the potential of synergistic combination therapy for prostate cancer.